ANALISIS YURIDIS TERHADAP PERTANGGUNGJAWABAN NEGARA AKIBAT PENCEMARAN UDARA LINTAS BATAS NEGARA - Astra, Rendy; Lenny Husna (SCIENTIA JOURNAL, 2022)
Air pollution is a problem that currently still occurs in the Southeast Asia region, which is the result of forest fires, the impact of which is directly felt by two other neighboring countries, namely Malaysia and Singapore. As for in this paper, the author makes two formulations of legal issues regarding state responsibility in the Asean Agreement on Transboundary Haze Pollution (AATHP) and the responsibility of the Indonesian state for forest fires in the Sumatran Riau region. Based on the data and findings that the authors obtained in this study, Indonesia must carry out State Responsibility internationally as a country that has resulted in haze pollution as contained in Articles 35 to 37 of the 2001 ILC Draft concerning State Responsibility in the form of restitution, compensation, or satisfaction. And the conclusion contained in this journal is that the form of accountability carried out by the Indonesian state is a form of satisfaction or an official apology conveyed by the Indonesian government. Meanwhile, when Indonesia has ratified the AATHP agreement, automatically Indonesia and other participating countries are jointly responsible for the pollution of haze and smoke pollution in the Southeast Asian region. Keywords: State Accountability, Haze Pollution, Cross Borders